Conventional wisdoms (myths) versus realities about transforming and endogenously innovating food systems: Implications for re-alignment of policies - Reardon, Thomas (International Food Policy Research Institute, 2024)
This is a condensed version of a paper on conventional wisdom (myths) versus realities about transforming and endogenously innovating food systems. It was presented as a plenary talk at the Rethinking Food Markets Symposium on December 11, 2024. This note is structured as a sequence of research steps to better align policy with food system realities, as follows: Identify the conventional wisdom (CW), premises, assumptions as perceived by governments and donors about factors constraining proper food market system functioning and how to address these. Identify how CW influences government/donor actions (policies, investments, programs, external or exogenous innovations). Review evidence of actual food system functioning: (c.1) patterns in structure, conduct, performance; (c.2) transformations in those three; (c.3) endogenous innovations by system actors to address constraints. Assess whether/how CW matches (or contradicts) reality. If there is gap or contradiction, identify two things: (e.1) What kind of problem/error generated by the gap between CW and reality: (i) led to lack of needed action (neglect); (ii) led to wrong action (mistake); (iii) led to action redundant with “endogenous innovations” that real world actors already doing (not needed). (e.2) What actions would be better and would be better aligned with discovered food system realities and endogenous innovations - and improve the situation. The rest of the paper lays out findings from the case studies as conducted through the Rethinking Food Markets initiative, as well as other recent empirical research that illustrates points relevant to the above five steps.